TINDAK PIDANA PENIPUAN TERHADAP MODUS PERDUKUNAN PALSU - Novita (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2016)
In the era of globalisation and development of technology today does not immediately change the mindset of society to think rationally and modern. Still many circles of the Indonesian people, without exception, educated or not, who believe in mystical things. As well as criminal fraud by fake shamanism mode, which is where the victim not only of the poor people, but also from among the educated and whealthy. They use the help of shaman to smoothen their business, career, marriage and finances, etc. A case as example, the case of fake shamanism with doubling the money motive.